Analisis Perbedaan Tingkat Suku Bunga pada Perhitungan Jaminan Hari Tua (JHT) - Ning Eliyati; Endang Sri Kresnawati; Yulia Resti; Fitri Puspasari (Faculty of Mathtmatics and Natural Sciences, 2016)
The purpose of this paper is to analyze the difference in interest rates on the calculation of pension funding. The interest rate varies grouped based on the rules set by the fuzzy numbers trapezoidal membership function. The results showed that the trapezoidal membership function and value of tolerance 0.02 earned four interest rate is 3.76%, 5.76%, 11.83% and 13.83%. The lower the interest rate, the lower the pension contribution paid, as well as actuarial liabilities, and conversely, the greater the interest rate, old age insurance contributions and actuarial liabilities is getting smaller.